Formation mechanism of hierarchical structure of crystal morphology in a sessile droplet - Kouki Morinaga; Marie Tani; Rei Kurita (Physical Review Research, 2020)
Crystal patterns formed by evaporation play important roles in industrial technologies. Recently, it was found that a concentric pattern and an orchid pattern may be seen when a pinned sessile droplet dries. Due to complex coupling between evaporation and crystallization, the mechanism behind this unique recrystallization phenomenon is yet to be determined. Here, we investigate the formation of these macroscopic patterns using microscopy. Then we show that diffusion-limited aggregation, absorption, and dewetting from the substrate all play a role in its development. In addition, it is found that anisotropy of the core is a key parameter for the pattern formation on a long length scale.